2012
DOI: 10.1021/jm301039c
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of Bicyclic Iminopyrimidinones As Beta Amyloid Cleaving Enzyme-1 (BACE1) Inhibitors: Conformational Constraint to Favor a Bioactive Conformation

Abstract: On the basis of our observation that the biaryl substituent of iminopyrimidinone 7 must be in a pseudoaxial conformation to occupy the contiguous S1-S3 subsites of BACE1, we have designed a novel fused bicyclic iminopyrimidinone scaffold intended to favor this bioactive conformation. Strategic incorporation of a nitrogen atom in the new constrained ring allowed us to develop SAR around the S2' binding pocket and ultimately resulted in analogues with low nanomolar potency for BACE1. In particular, optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 71 publications
0
50
0
Order By: Relevance
“…In the past decades, many X-ray structures of the apo BACE1 and the BACE1-inhibitor complex have been deter-www.nature.com/aps Wang YY et al Acta Pharmacologica Sinica npg mined, which provide detailed information about the structure and functional analysis of BACE1 [11][12][13][14][15][16] . BACE1 is a membraneanchored aspartic protease containing three distinct domains: an N-terminal ectodomain, a single transmembrane domain, and a cytosolic C-terminus.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, many X-ray structures of the apo BACE1 and the BACE1-inhibitor complex have been deter-www.nature.com/aps Wang YY et al Acta Pharmacologica Sinica npg mined, which provide detailed information about the structure and functional analysis of BACE1 [11][12][13][14][15][16] . BACE1 is a membraneanchored aspartic protease containing three distinct domains: an N-terminal ectodomain, a single transmembrane domain, and a cytosolic C-terminus.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the potency of BACE1 inhibitors, structure-based evolution combined with conformational constraint strategy of these lead compounds 3, 5, 7, 9 and 11 was performed to facilitate access to the prime side of the BACE1 active site, which provided the discovery of the corresponding conformationally restricted analogues (such as 3-hydroxypyrrolidine 4 [16], imidazo[1,2-a]pyridine 6 [17], pyrrolidine 8 [18], bicyclic iminopyrimidinone 10 [19] and chiral cyclopropanes 12a-c [20,21]; Figure 1). …”
Section: Advantages Of the Conformation Restriction Strategymentioning
confidence: 99%
“…Conformational restriction: an effective tactic in 'follow-on'-based drug discovery Review fied as an orally active, brain penetrant molecule that can lower amyloid-β (Aβ)40 in the plasma, cerebrospinal fluid and cortex of rats in a dose-dependent manner (Figure 1) [19]. Furthermore, γ-secretase modulators have emerged as a potential disease-modifying treatment for AD.…”
Section: Key Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Merck researchers have developed several lead compounds that were identified through screening of a million compounds from drug libraries, and these have produced a large number of molecules that potently inhibit BACE1 in vitro. [107][108][109][110][111] Trials of selected drugs in primate models have shown very promising potential, with near-complete inhibition of Aβ levels in the brain and CSF. 112,113 Compound MK-8931 has now progressed to Phase II clinical trials, and presentations at conferences suggest this is currently the most advanced BACE1 inhibitor in human trials.…”
Section: Bace1 Inhibitors In Preclinical and Clinical Trialsmentioning
confidence: 99%